Review of solutions for elastic data transmission in heterogeneous computer networks - Hvozdetska, K. P. (ХНУРЕ, 2021)
The use of a large number of different network devices is a pattern within Industry 5.0. Increasing volumes of data lead to congestion in existing networks. The work is devoted to the review of solutions to the problem of elastic data transmission in heterogeneous networks and ways to avoid this kind of congestion.
Keywords: Industry 5.0; Heterogeneous network; Data transmission